PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL KOOPERATIF TIPE JIGSAW BERBASIS KURIKULUM 2013 PADA MATA PELAJARAN SISTEM PENDINGINAN BAHAN BAKAR DAN PELUMAS DI SMKN 3 SENDAWAR - Batoq, Igidius; Susila, I Wayan; Rijanto, Tri (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2015)
ABSTRACT This research aims to find the learning set by using Jigsaw type as cooperative model bised on the 2013curriculum of the syllabus, lesson plan, students? worksheet, scoring sheet, learning media, studens? book, and the questions in the pretest and post test, to improve the student?s study achievement at SMKN 3 Sendawar. The learning set is developed through Research and development by using 4-D model that define, design, develop, and tried it out in the classroom by using 0ne-Group Pretest-Posttest Design. The result of the research shows that the validity of the syllabus, lesson plan, students? worksheet, scoring sheet, learning media, students? book, and the questions in the pretest post test get the index score V from Aiken ? 0,70 in the category of valid an faesible to be used in the research. The implementation of the Jigsaw type as the cooperative learning set is good enough, and the everage reliability of the instrument is 98,33%. The students? activity in the maeeting 1,2, and 3 get the average score of 3.67 in the category of very active. The students? response for the learning process is in the range of 71-73 and the number of the absolute frequency of 33,3% of the students do agree with the learning model. The improvement of the average students? study result in their cognitive is 0.72 (high gain). Overall, 93.3% of the students pass the learning process. Based on the data analysis, it can be councluded that Jigsaw type as learning medel which based on the 2013 curriculum by using scientific approach can improve the student? study resul at SMKN 3 Sendawar. Keywords : Jigsaw types as cooperative learning,2013 Curriculum, Learning set.